The Predatory Mites (Phytoseiidae, Parasitiformes) in the Fauna of Ukraine: of the Genera Paragigagnatus, Carinoseius, Kampimodromus, Eharius, Typhlodromips, and Euseius - Kolodochka , L. A. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2023)
Phytoseiid mites (Phytoseiidae, Parasitiformes) are well known as effective predators that are successfully used for biological control of plant pests. Despite significant progress in finding and using effective species of these mites in the practice of plant protection, in general, the amount of knowledge about this important group of small arthropods remains insufficient. This article continues previous publications about research results, some of which were published earlier (Kolodochka, 2022; 2023). The article summarises the results of the study of the species composition of phytoseiid mites of six genera conducted in Ukraine over the past decades, namely, Paragigagnatus Amitai & Grinberg, Carinoseius Wainstein, Kampimodromus Nesbitt, Eharius Tuttle & Muma, Typhlodromips De Leon, Euseius Wainstein. It provides the main elements of the characteristics of these taxa: detailed species redescriptions are accompanied by species identifiers, drawings, morphological data and measurements, diagnoses, places of storage of types, data on the distribution of species in the world and Ukraine, places of residence, estimation of abundance etc.